Issues, Challenges, and Potential of Palliative Care in Pediatric Nursing: A Systematic Review - Widiyanto, Aris; Handayani, Rina Tri; Atmojo, Joko Tri (Journal of Maternal and Child Health, 2020)
Background: Palliative care is an essential right for infants and children with a life-threatenÂing illÂness. However, palliative care is still unÂavaÂilÂable in some developing countries. This stuÂdy aimÂed to explore the issues, challenges, and poÂtenÂtial of palliative care in pediatric nursing care.Subjects and Method: A systematic review was conducted by searching published articles in PubMed, CINAHL, and EMBASE databases, from year 2000 to 2018. The keywords used for this stuÂdy included â€œpalliativeâ€ AND â€œchildrenâ€, â€œpalÂliaÂtiveâ€ AND â€œnursingâ€ AND â€œcareâ€, â€œpalliative caÂreâ€ AND â€œpediatric careâ€. The data were analyzed by PRISMA flow diagram.Results: Palliative care is evolving continuously, meeting new challenges, and expandÂing beyond the care of terminally ill pediatric patients. A maÂjor challenge in palliative care is effective comÂmuÂÂnication. However, only a few communication trainings exist for nurses. Obstacles of palliative care in pediatrics nursing included clinical, opeÂraÂtional, and financial factors. However, palliaÂtive care has a substantial potential to reduce morbidity in infants and children. In addition, a cohort study conducted in 265 pediaÂtric cancer patients reported that palliative care reduced pain and improved their life expectancy.Conclusion: Palliative care is a comprehensive appÂroach of care and its delivery to pediatric paÂtients is challenging. It has a substantial potential in reducing infant and child morbidity.Keywords: palliative care, pediatric nursing, palÂliÂative nursingCorrespondence:Â Aris Widiyanto. School of Health Sciences MamÂba'ul 'Ulum, Surakarta, Jl. Ring Road Utara, TaÂwangsari, Mojosongo, Jebres, Surakarta, Central Java. Email: widiyantoaris99@gmail.com. MoÂbile: 081329209095Journal of Maternal and Child Health (2020), 5(1): 167-172https://doi.org/10.26911/thejmch.2020.05.02.06